Teilhard de Chardin and the Cosmic Life: hundred years after - Sequeiros, Leandro (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Summary: On the year 1916, Teilhard de Chardin has already been for more than one year working as a stretcher carrier, at the war front. It is then that the «teilhardian genius» unfolds. His first essay of spiritual, philosophic and mystic type is «The Cosmic Life», the centenary of which falls in 2016. In this work we offer the context in which this essay was elaborated by the writer, and also we present the more outstanding ideas of the author, together with some clarifying and critical notes. In another place, we offer the complete text in a new translation, realized from the French text of Teilhard’s Works.
Keywords: Teilhard de Chardin; spirituality; mystic; cosmovision; cosmic; The Great War; Evolution; Matter